Register Used by Indonesian E-sport Team (Onic) in Mobile Legend Bang-Bang - Yosua Ade Putra; Nicholas Lee; Belly Oktapianto; Endar Rachmawaty Linuwih (Universitas Kapuas, 2024)
Register refers to a form of language variation specific to a particular community or group. Different language varieties within a community can convey distinct meanings. This paper aims to identify the forms of registers used by pro players from the Onic e-sports team in the online game Mobile Legends: Bang Bang and to explain their functions. The data found were 18 registers used by pro players to communicate in the team. The form of the register is classified into two: lingual units of word as many as 15 registers and lingual units of phrase consisting of 3 registers. From these registers there are three functions, namely; a) enhancing communication efficiency, b) boosting hype and atmosphere, and c) facilitating communication among players. Studying these registers is significant as it sheds light on the unique linguistic dynamics of gaming communities, contributing to a deeper understanding of language use in digital and collaborative environments.